Revisiting the law regarding sentences of kidnapping in Malaysia: an analysis / Nurul Farhana Adnan, Afaf Abdul Rahman and Siti Ridha Fateha Razali - Adnan, Nurul Farhana; Abdul Rahman, Afaf; Razali, Siti Ridha Fateha (Faculty of Law, 2014)
In Malaysia, the crime of kidnapping is getting out of hand. Due to the rising number of kidnapping cases in this country, we are intrigued to further analyze whether the punishments meted out to the kidnappers are adequate to reduce the rate of kidnapping cases in Malaysia. This paper attempts to examine how Malaysia operates the law of kidnapping by observing the punishment given to the kidnappers upon conviction. The analysis of this paper will predominantly consist of two parts. The first part will identify the laws applied in Malaysia in order to punish the kidnappers and secondly, whether the increase amount of punishment for kidnapping crime, specifically under Section 363 of the Penal Code, will reduce the kidnapping rate in Malaysia.